Antenatal depression screening and perintal depression among women at Rahima Moosa Hospital - Marsay, Carina (My University, 2018)
In South Africa, 30-40% of women suffer from perinatal depression. This has devastating consequences for both mother and infant, as depressed mothers are at higher obstetric risk and have diminished capacity to care for the physical and emotional needs of their infants. Without adequate screening, approximately 75% of women with perinatal depression will remain undiagnosed and only 10% of these women will receive treatment. Studies conducted in low, middle and high income settings have shown that it is feasible and acceptable to incorporate mental health screening and depression assessment, with referral, into antenatal clinics. The study reported in this dissertation aimed to investigate whether women attending the antenatal clinic at Rahima Moosa Hospital would benefit from antenatal screening for perinatal depression. This would be achieved by determining whether antenatal screening for depression lead to reduced symptoms of depression. In addition, the study was designed to compare the specificity and sensitivity of the Whooley screening questions with the Edinburgh Postnatal Depression Scale (EPDS) in detecting major depression during pregnancy. Lastly, the study aimed to explore the lived experiences, and barriers to care, of women identified as suffering from perinatal depression who were referred for further management. A mixed-method, explanatory design, involving three phases, was used. In the first phase, data were collected using quantitative measures, including a standardised biographical interview, the EPDS, the Whooley screening questions and the Structured Clinical Interview of DSM5. During the second and third phases, quantitative measures were used again to identify changes from phase one. Data were also collected using qualitative indepth interviews to explain results in greater depth. Perinatal depression is a significant public health problem that needs to be addressed in order to improve maternal and child health. Only by listening to the needs of women experiencing perinatal depression can mental health care be improved within obstetric services. Welldesigned research studies which use an explanatory, transformative design can be used to guide effective screening programmes, improve treatment and inform national policy.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, Johannesburg 2018
Keywords: Pregnancy Complications; Prenatal Care; Pregnancy; Depression